2018
DOI: 10.21147/j.issn.1000-9604.2018.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MRI versus 18F-FDG PET/CT: Which is better in differentiation between malignant and benign solitary pulmonary nodules?

Abstract: DCE-MRI can be used to differentiate between benign and malignant SPNs and has the advantage of being radiation free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
3
2
Order By: Relevance
“…Our study is one of the few that investigated the capability of Tofts derived DCE parameters in distinguishing malignant and benign nodules. Unlike prior studies, our study demonstrated that none of the DCE measurements independently predicted malignancy and there was poor intra‐ and interobserver agreement. Since none of the prior studies included a substantial number of groundglass or part‐solid nodules that we examined, it is uncertain whether our findings reflect differences in our cohorts' composition.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study is one of the few that investigated the capability of Tofts derived DCE parameters in distinguishing malignant and benign nodules. Unlike prior studies, our study demonstrated that none of the DCE measurements independently predicted malignancy and there was poor intra‐ and interobserver agreement. Since none of the prior studies included a substantial number of groundglass or part‐solid nodules that we examined, it is uncertain whether our findings reflect differences in our cohorts' composition.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results confirm prior reports promoting MRI as a useful noninvasive means for imaging pulmonary nodules without the use of ionizing radiation . Akin to findings in our prior study and dissimilar to other studies, our current study showed that the ADC of malignant lesions is higher than that of benign lesions, even though our numeric ADC threshold is similar to other studies.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…According to analysis, such result was perhaps caused by active tumor vascular proliferation and a sharp increase in microvessel density inside the malignant SPN [ 21 ]. The WR in the time-signal curve of the MRI image is relevant to interstitial diseases (resilience and collagenous fiber) [ 22 ]. The study result herein showed that there was no statistical difference in WR values in the time-signal curve of MRI images of the two groups of patients ( P > 0.05), which was consistent to the research result of Guan et al [ 23 ].…”
Section: Discussionmentioning
confidence: 99%